Pemberian Posisi Semi-Fowler Untuk Meningkatkan Saturasi Oksigen Pasien Congestive Heart Failure Di ICU RSUD Tidar Magelang - Muhammad Iqbal Rahmawan; Al-Afik; Enggar Rubidiyani (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Congestive Heart Failure (CHF) is a condition where the heart function is disturbed and is unable to pump enough blood that causes the heart to not provide oxygen to meet the needs of the tissue so that the patient experiences shortness of breath or dyspnea. Objective: To implement a nursing intervention for providing a Semi-fowler position to increase the oxygen saturation on the Congestive Heart Failure patient with dyspnea. Method: This study was a case report (case report) with nursing intervention providing Semi-fowler position, was carried out for 3 times on different days. Results: The oxygen saturation before granted a semi-fowler position on the first and second observations were 94% then on the third observations were 95%. Later after 3 times provided a semi-fowler position, the oxygen saturation up to 98% at the first-time observation and 99% at the second and on the third observation. Conclusion: there is an increase in oxygen saturation on the Congestive Heart Failure patient with dyspnea after 2 times given a semi-fowler position on a different day.